MEDIA PEMBELAJARAN BERBASIS CANVA UNTUK MENINGKATKAN MINAT BELAJAR IPA DI MADRASAH IBTIDAIYAH (MI) - Ria Aryani; Zahra Zahra; Fitriyah Fitriyah; Mabruri Mabruri (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
The low interest in learning and the difficulty elementary school students face in understanding science material that tends to be theoretical and boring are the background to this research. This problem requires the use of digital instruments to stimulate the various senses of elementary school children in digesting the material contextually. The focus of this research is to examine the implementation of Canva platform-based learning media in increasing science learning interest in Madrasah Ibtidaiyah. The research method applied is library research using a qualitative descriptive-analytical approach. Data collection was carried out through searching scientific documents from Google Scholar, followed by data reduction and in-depth content analysis techniques. The research findings show that Canva is able to concretize abstract science concepts through infographics, animations, and interactive videos that stimulate students' cognitive and psychomotor aspects. The variety of visual features on this platform has proven effective in creating a varied and enjoyable learning atmosphere and is able to significantly reduce learning boredom. The main conclusion of the study confirms that the use of Canva media is very strategic in boosting student interest and active engagement in the classroom. However, the success of optimizing this digital platform depends heavily on the methodological creativity of teachers and the readiness of supporting facilities such as a stable internet network. ABSTRAK Rendahnya minat belajar serta kesulitan siswa sekolah dasar dalam memahami materi sains yang cenderung teoritis dan membosankan melatarbelakangi penelitian ini. Masalah tersebut menuntut adanya pemanfaatan instrumen digital guna menstimulasi berbagai indera anak usia dasar dalam mencerna materi secara kontekstual. Fokus penelitian ini adalah mengkaji implementasi media pembelajaran berbasis platform Canva dalam meningkatkan minat belajar IPA di Madrasah Ibtidaiyah. Metode penelitian yang diterapkan adalah studi kepustakaan (library research) menggunakan pendekatan kualitatif deskriptif-analitis. Pengumpulan data dilakukan melalui penelusuran dokumen ilmiah dari Google Scholar, yang dilanjutkan dengan reduksi data dan teknik analisis isi (content analysis) secara mendalam. Temuan penelitian menunjukkan bahwa Canva mampu mengonkretkan konsep sains yang abstrak melalui infografis, animasi, dan video interaktif yang merangsang aspek kognitif serta psikomotorik siswa. Ragam fitur visual pada platform ini terbukti efektif menciptakan suasana belajar yang variatif, menyenangkan, serta mampu menurunkan kejenuhan belajar secara signifikan. Simpulan utama penelitian menegaskan bahwa penggunaan media Canva sangat strategis dalam mendongkrak minat dan keterlibatan aktif siswa di kelas. Meski demikian, keberhasilan optimalisasi platform digital ini sangat bergantung pada kreativitas metodologis guru serta kesiapan sarana pendukung seperti kestabilan jaringan internet.